Thermoregulation in captive broad-snouted caiman (Caiman latirostris) - Bassetti, Luís A. B. (2014)
Background: Crocodilians are ectothermic animals. For this reason, the environmental temperature has substantial effects on their physiology and behavior. The thermoregulatory behavior of these animals involves the selective use of different types of environments. This behavior enables them to reach the temperature level for their metabolic activities. This study aimed to determine the influence of sex, body size, and reproductive stage on the body temperature (T b) of adult broad-snouted caiman (Caiman latirostris) in captivity. Thermal sensors were surgically implanted in the peritoneal cavity of 16 adult females and 4 adult males and programmed to register T b hourly during 6 months. Results: The diel T b pattern of the broad-snouted caiman reflected the variation among the microenvironmental temperatures used by the species (water surface, pool bottom, and ground). The sex of the animals had influence on their T b, but body size did not. Reproductive females had higher T b than non-reproductive females during October to early November. It is possible that this difference is a result of the ovulation period of the species. Sick animals appeared to show behavioral fever. Conclusions: The results of the present study suggest that several factors can affect the T b of adult broad-snouted caiman in captivity. Future studies should focus on the possible effect of thermoregulatory behavior on individuals' growth rate and reproductive performance.